Best Practices for Implementing Management Information Systems: Implementation of the Nusantara Integrated Information Service (LITERA) at the Nusantara Islamic University, Bandung - Mia Lisartika; Mulyawan Safwandy Nugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Management Information Systems (SIM) have become an important element in efforts to increase the efficiency and effectiveness of various educational institutions. SIM is used as an information center for educational services, especially in universities. This research is descriptive qualitative research. Data collection was carried out through observation, interviews and documentation. The research results show that the Islamic University of Nusantara Bandung has used a management information system called LITERA (Integrated Information Services Archipelago). This management information system is in the form of a website that provides a literature menu, new students menu, tracer studies menu and a repository menu.